The Role of the Art of Calligraphy and Its Influence on The Formation of Students’ Spiritual Values at UIN Walisongo Semarang - Nadia Khoirun Navila (CV Projurnal Mitra Publikasi, 2025)
The formation of students’ spiritual values necessitates supportive activities beyond the formal curriculum, where the art of calligraphy is regarded as a transcendental medium involving the profound appreciation of sacred texts. This study aims to explore the role of calligraphy practices within the Student Activity Unit (UKM) LDK Arofah at UIN Walisongo Semarang and interpret how these practices contribute to the internalization of students’ spiritual character. Employing a qualitative approach with descriptive-analytical field research, primary data were gathered through in-depth interviews, participant observation, and documentation involving key informants from various faculties. Data analysis focused on mapping the transition of values from the artistic realm to the domain of worship using the Miles, Huberman, and Saldaña interactive model. The findings suggest that calligraphy serves as a significant and consistent medium for spiritual training (mujahadah) and informal dhikr, transcending its aesthetic dimensions. This spiritual engagement is reflected in three integrated thematic pillars: the enhancement of taqarrub ila Allah through the appreciation of sacred texts; the development of discipline and istiqomah through the internalization of technical precision; and the cultivation of inner peace (jamāl) through transcendental reflection. Ultimately, calligraphy functions as a holistic catalyst that harmonizes outward artistic excellence with inward spiritual quality, strengthening the moral foundations of students.